2020
DOI: 10.3390/molecules25225459
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Antitumor Activity of a Series of Novel 4-(Aromatic Sulfonyl)-1-oxa-4-azaspiro[4.5]deca-6,9-dien-8-ones

Abstract: Many sulfonamides show anticancer activity. Based on benzenesulfonylazaspirodienone (HL-X9) identified in our previous work, we optimized the lead compound for better efficacy, thereby synthesizing a series of novel 4-(aromatic sulfonyl)-1-oxa-4-azaspiro[4.5]deca-6,9-dien-8-one derivatives through a key step of metal-catalyzed cascade cyclization. The preliminary antiproliferative tests have shown that the anticancer activities of acetyl-protected mannose-linked sulfonylazaspirodienone derivatives (7i–7l) have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…1). In addition, Sulfonyl or sulfonamide hybrids were broadly explored for their anticancer activities via different mechanisms [8][9][10][11][12][13][14][15][16][17] and it was found that they possess minimum side effects along with multi-drug resistance activity. Therefore, and in continuation of our interest to develop a series of novel small molecules as potential antitumor agents that can block biologically relevant molecular targets [18][19][20][21][22] , we prepared certain pyrazoles, pyridines, thiazoles derivatives containing sulfonamide pharmacophores and studied their activity against breast cancer cell line (MCF-7).…”
Section: Introductionmentioning
confidence: 99%
“…1). In addition, Sulfonyl or sulfonamide hybrids were broadly explored for their anticancer activities via different mechanisms [8][9][10][11][12][13][14][15][16][17] and it was found that they possess minimum side effects along with multi-drug resistance activity. Therefore, and in continuation of our interest to develop a series of novel small molecules as potential antitumor agents that can block biologically relevant molecular targets [18][19][20][21][22] , we prepared certain pyrazoles, pyridines, thiazoles derivatives containing sulfonamide pharmacophores and studied their activity against breast cancer cell line (MCF-7).…”
Section: Introductionmentioning
confidence: 99%
“…37 As a result, it is viable to expand a sequence of sulfonamides with alkyl amide side chain amendment on carboxyl for enhanced antibacterial e ciency. Sulfonamides have medicinal applications and many of them are broadly utilized in therapeutic as antimicrobial 38 , antitumor [39][40] , anticancer 41 , antiviral 42 , anti-HIV 43 , antidiabetic 44 , antimalarial 45 , antitubercular 46 , analgesic 47 , antioxidant 48 , antihypertensive 49 , antileishmanial 50 , anti-in ammatory 51 , anticonvulsant 52 , diuretic 53 , anti-carbonic anhydrase 54 and antiplatelet. 55…”
Section: Introductionmentioning
confidence: 99%
“…1). In addition, Sulfonyl or sulfonamide hybrids were broadly explored for their anticancer activities via different mechanisms [8][9][10][11][12][13][14][15][16][17] and it was found that they possess minimum side effects along with multi-drug resistance activity. Therefore, and in continuation of our interest to develop a series of novel small molecules as potential antitumor agents that can block biologically relevant molecular targets [18][19][20][21][22] , we prepared certain pyrazoles, pyridines, thiazoles derivatives containing sulfonamide pharmacophores and studied their activity against breast cancer cell line (MCF-7).…”
Section: Introductionmentioning
confidence: 99%